Global Policy and Global Economy: The Expected Surprises of the First Half of 2019 - V. A. Shamakhov (Управленческое консультирование, 2019)
The first half of 2019 forces to remember the known law on transition of quantitative changes to qualitative. Any essentially new trends were not shown, the new facts did not drop out of a traditional information picture, but did it more relief. However there are all bases to say that not really new trends lead us to formation of a bit different system of the relations in economy and policy.